Association between Socioeconomic Status and Motor Skill Development among Preschool Children of Lekhnath, Pokhara: A Cross-Sectional Study - Shrestha, Ripti; Yadav, Bijendra Prasad; Amatya, Neebha; Rana, Rajab; Prajapati, Rajesh (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Gross and fine motor skills are both necessary for healthy growth. According to studies, children from lower “Socioeconomic Status (SES)” families have delayed development of these fundamental motor skills, placing them at risk for delayed motor skill development. The current research’s objective was to study the occurrence of developmental risks and the variances between the gross as well as fine motor growth related to the SES of pre-schoolers in Pokhara. MATERIALS AND METHODS: One district preschool in the Lekhnath municipality of Pokhara was selected for the study. 102 elementary school students between 3-6 years were evaluated. Children’s fine and gross motor skill and SES of their parents were calibrated. The values were compared and evaluated for the various economic status and genders keeping p<0.05 as significant. RESULTS: Particularly in the area of fine motor abilities, significant variations between the SES groups were found. Gross motor growth had a greater variation and was substantial than fine motor skill. Fine motor growth risk prevalence ranged from 1.9% to 21.0%, while gross motor growth risk prevalence peaked at 14.63%. Age and sex also affected the prevalence rates. CONCLUSIONS: In pre-schoolers aged three to six, fine motor skills are strongly correlated with socioeconomic level. A correlation in gross motor skills was not established. In this study, sex had a greater impact on motor development than SES